Knowledge Management and Organizational Performance of Nepalese Commercial Banks (The Batuk, 2020)
This paper attempts to examine the effects of knowledge management on organizational performance of Nepalese commercial banks. Data are collected through structured questionnaire from 300 respondent of Kathmandu valley. Descriptive and casual comparative research designs are used to achieve the objectives and descriptive statistics as well as multiple regression models have been used to analyze the data. It is observed that organizational performance will be better provided that appropriate knowledge management ensured. Knowledge acquisition, knowledge sharing, knowledge storing, information technology and organizational culture have positive effect on organizational performance.